2020
DOI: 10.3390/plants9091087
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Phytochemicals Isolated from Akebia quinata Enhances Glucose-Stimulated Insulin Secretion by Inducing PDX-1

Abstract: Chocolate vine (Akebia quinata) is consumed as a fruit and is also used in traditional medicine. In order to identify the bioactive components of A. quinata, a phytosterol glucoside stigmasterol-3-O-β-d-glucoside (1), three triterpenoids maslinic acid (2), scutellaric acid (3), and hederagenin (4), and three triterpenoidal saponins akebia saponin PA (5), hederacoside C (6), and hederacolchiside F (7) were isolated from a 70% EtOH extract of the fruits of A. quinata (AKQU). The chemical structures of isolates 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Polypeptide-p isolated from Momordica charantia , a bioactive natural ingredient from herbal medicine, has been reported to act as insulin [ 6 ], and epicatechin isolated from Pterocarpus marsupium induces pancreatic islet β-cell regeneration [ 7 ]. S-methylcysteine sulfoxide isolated from Allium cepa [ 8 ], Momordicoside U isolated from Momordica charantia [ 9 ], stigmasterol-3- O -β- d -glucoside isolated from the fruit of Akebia quinata [ 10 ], formononetin isolated from Astragalus membranaceus [ 11 ], and hypoxylonol F isolated from Annulohypoxylon annulatum [ 12 ] have been reported as bioactive compounds that increase insulin secretion from pancreatic islet β-cells. These bioactive natural ingredients that increase insulin secretion also enhance the expression of proteins related to the regulation of pancreatic β-cell survival and function, such as peroxisome proliferator-activated receptor-γ (PPARγ), insulin receptor substrate-2 (IRS-2), phosphatidylinositol 3-kinase (PI3K), Akt, and pancreatic and duodenal homeobox-1 (PDX-1).…”
Section: Introductionmentioning
confidence: 99%
“…Polypeptide-p isolated from Momordica charantia , a bioactive natural ingredient from herbal medicine, has been reported to act as insulin [ 6 ], and epicatechin isolated from Pterocarpus marsupium induces pancreatic islet β-cell regeneration [ 7 ]. S-methylcysteine sulfoxide isolated from Allium cepa [ 8 ], Momordicoside U isolated from Momordica charantia [ 9 ], stigmasterol-3- O -β- d -glucoside isolated from the fruit of Akebia quinata [ 10 ], formononetin isolated from Astragalus membranaceus [ 11 ], and hypoxylonol F isolated from Annulohypoxylon annulatum [ 12 ] have been reported as bioactive compounds that increase insulin secretion from pancreatic islet β-cells. These bioactive natural ingredients that increase insulin secretion also enhance the expression of proteins related to the regulation of pancreatic β-cell survival and function, such as peroxisome proliferator-activated receptor-γ (PPARγ), insulin receptor substrate-2 (IRS-2), phosphatidylinositol 3-kinase (PI3K), Akt, and pancreatic and duodenal homeobox-1 (PDX-1).…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin can induce the expression of PDX-1 gene to increase serum insulin levels and decrease serum glucose levels [ 146 ]. Andrographolide, naringin, and Akebia quinata can also enhance insulin secretion and alleviate β-cell dysfunction by targeting PDX-1 [ 147 , 148 , 149 ].…”
Section: Pdx-1 and The Reversal Of T2dmmentioning
confidence: 99%
“…In T2DM, dysfunctional pancreatic β-cells exhibit reduced insulin secretion, an indicator of disease progression. PDX-1 and MafA genes are involved in development of pancreatic β-cells and transcription of the insulin gene [6]. To further analyze protective effects of JTTF treatment on pancreatic β cells, INS-1 cells were exposed to high-glucose conditions.…”
Section: Jttf Upregulates Insulin Biosynthesis and Expression Of Insulin-related Genes By Ins-1 Cellsmentioning
confidence: 99%
“…Importantly, numerous studies have demonstrated that longterm exposure of pancreatic β-cells to high glucose (HG) levels induces cell dysfunction and apoptosis, thus impairing insulin secretion function and promoting eventual development of T2DM [5]. Aside from strategies to reduce insulin resistance or promote GSIS by increasing hepatic glucose output, maintenance of healthy pancreatic β cell function is another strategy for preventing T2DM [6], since dysregulated pancreatic β-cells play critical roles in T2DM pathogenesis [7] . Recently, Traditional Chinese Medicine (TCM) has gained attention as an important source of potential bioactive compounds for use in preventing or treating T2DM.…”
Section: Introductionmentioning
confidence: 99%